Management of Severe and Severe/Complicated Clostridoides difficile Infection Using Sequential Fecal Microbiota Transplant by Retention Enema. (21st January 2021) - Rupawala, Abbas Hatim; Gachette, Darrel; Bakhit, Mena; Jimoh, Lanre; Kelly, Colleen R
Abstract: We evaluated serial fecal microbiota transplant (FMT) by retention enema in patients with severe or severe/complicated Clostridoides difficile infection (CDI) unresponsive to at least 48 hours of standard antibiotic therapy. Of the 15 patients included, despite initial improvement in most patients, only 5 patients sustained cure at 30 days, and serious adverse events occurred in 4 patients.